PENGARUH MEDIA TANAM DAN PEMUPUKAN NPKTERHADAP PERTUMBUHAN BIBIT DAMAR MATA KUCING (Shorea javanica) - Fitri Kurniawati; Miranti Ariyani (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Effect of Growing Media and NPK Fertilizer on Growth of Shorea Javanica. Cibodas botanical garden – LIPI had compost product based on organic waste material (litter, grass, twigs, and fruit) which were collected from garden. Compost was produced by two methods : using katalek bioactivator and natural compost without bioactivator. Utilization of compost as growing media at nursery unit botanical garden was not optimal. The objective of this research was to determine the ability of compost from botanical garden as a growing media for seedling collection at Cibodas botanical garden. This study was conducted using a Randomized Block Design (RAB) with six treatments and four replications using Shorea javanica as plants indicator. Three types of growing media (top soil, natural compost and katalek compost) were applied for the treatment with the addition or non addition of NPK fertilizer. However, control treatment was made from top soil without addition of NPK. The data showed that both natural compost and katalek compost were demonstrated better result than top soil growing media. Katalek compost without addition of NPK fertilizer gave significantly different result at enhancement of plant height, leaf number, and dry weight if compared with control.